2022
DOI: 10.3390/v14020191
|View full text |Cite
|
Sign up to set email alerts
|

A Brief History of Giant Viruses’ Studies in Brazilian Biomes

Abstract: Almost two decades after the isolation of the first amoebal giant viruses, indubitably the discovery of these entities has deeply affected the current scientific knowledge on the virosphere. Much has been uncovered since then: viruses can now acknowledge complex genomes and huge particle sizes, integrating remarkable evolutionary relationships that date as early as the emergence of life on the planet. This year, a decade has passed since the first studies on giant viruses in the Brazilian territory, and since … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…It took the discovery of the giant Mimivirus ( La Scola et al, 2003 ) to emphasise how flawed this ‘filterable’ assumption was. Since discovering viruses could be as complex as cells, scientists have found that giant viruses are abundant in many ecosystems ( Al-Shayeb et al, 2020 ; Moniruzzaman et al, 2020 ; Boratto et al, 2022 ). In a demonstration of the power of a paradigm to influence the way that discoveries are interpreted, the largest known viruses, the Pandoraviruses, were not recognised as viruses when first discovered but rather were described as ectosymbionts ( Scheid et al, 2008 ).…”
Section: Where Do the Undead Viruses Fit Into The Standard Evolutiona...mentioning
confidence: 99%
“…It took the discovery of the giant Mimivirus ( La Scola et al, 2003 ) to emphasise how flawed this ‘filterable’ assumption was. Since discovering viruses could be as complex as cells, scientists have found that giant viruses are abundant in many ecosystems ( Al-Shayeb et al, 2020 ; Moniruzzaman et al, 2020 ; Boratto et al, 2022 ). In a demonstration of the power of a paradigm to influence the way that discoveries are interpreted, the largest known viruses, the Pandoraviruses, were not recognised as viruses when first discovered but rather were described as ectosymbionts ( Scheid et al, 2008 ).…”
Section: Where Do the Undead Viruses Fit Into The Standard Evolutiona...mentioning
confidence: 99%
“…Many GV also present fibrils (Figure 2) as APMV, such as: (1) tupanviruses, with a capsid of approximately 450 nm in diameter and a tail attached to it, both covered in fibrils, resulting in particles varying from 1.2 up to 2.3 µm in length; 19 (2) Cotonvirus japonicus, 28 a mimivirus isolate, with approximately 400 nm in diameter and also surrounded by surface fibrils of approximately 100 nm; (3) Marseillevirus, 13 with approximately 250 nm of diameter, and 12 nm fibrils surrounding its particles' surface; (4) PBCV-1, an algae infecting virus with approximately 190 nm in length and small fibrils around the capsid, of nearly 19 nm; 9 (5) orpheovirus, with particles larger in length than APMV (up to 1.1 µm), but presenting smaller fibrils when compared to these mimiviruses, as well as two tegument layers between the fibrils and the inner membrane; 29 (6) Mollivirus sibericum, 4 an almost spherical GV with 500-600 nm in diameter and surrounded by a fibrillar tegument as a mesh of fibrils; (7) cedratviruses, around 500 nm up to 1 µm in length, 16,30 whose viral factory can be divided in two, one being associated with its fibrils acquisition; and finally (8) Yasminevirus, 31 the first Klosneuvirus to be isolated and that presents a particle with approximately 330 nm covered by a thin layer of fibrils.…”
Section: Viral Fibrils: An Intriguing Structural Feature Among Giantsmentioning
confidence: 99%
“…However, the term "giant viruses" has also been used to refer to smaller nucleocytoviruses, with particles ranging from 150 to 500 nm. Giant viruses are ubiquitous and have already been isolated from different countries, [2][3][4][5] from different environmental 6,7 and clinical samples. 8 The first virus to be called a giant virus was Paramecium bursaria chlorella virus 1 (PBCV-1), which infects algae and which has particles up to approximately 190 nm in diameter, 9 and a dsDNA genome of approximately 330 kb.…”
Section: Introduction a Glimmer Of Microbial Evolution: Giants Among ...mentioning
confidence: 99%
“…Brazil is one of the countries with the highest biodiversity and species richness in the world [ 13 ]. Its tropical forests, such as the Amazon, are globally renowned for their complexity and their role in regulating the world’s climate.…”
Section: Introductionmentioning
confidence: 99%